CatalogToMakers: a collaborative cataloging platform for electronic components and physical computing projects related to musical creativity - Bastos, Michael L.; Calegario, Filipe C. A.; Cabral, Giordano R. E. (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
The Maker Movement is a growing reality in the new industry and academic community. It consists of the Do-It-Yourself (DIY) style-spreading proposal, emphasizing the creation and development of creative thinking. In this context, the democratization of the Internet has meant that non-expert users are capable of developing new hardware technologies. In the music context, the easy access to low-cost equipment and the large number of people sharing knowledge facilitate prototyping and extend the creation of digital musical instruments. However, the places where the information related to the components used in these projects are not centralized nor organized. Therefore, it makes access to this information difficult, slowing down and hindering the flow of creative development. Thus, to reduce this development time and facilitate access to this information, this paper describes the processes for designing the CatalogToMakers tool, a collaborative cataloging platform for electronic components, and physical computing projects focusing on musical creativity. This approach implements several essential functions to facilitate the conception process of hardware development. Finally, an evaluation focused on non-expert users showed promising results.